Ternary PtRuCu aerogels for enhanced methanol electrooxidation. Issue 22 (29th May 2019) - Wang, Hengjia; Wu, Yu; Luo, Xin; Jiao, Lei; Wei, Xiaoqian; Gu, Wenling; Du, Dan; Lin, Yuehe; Zhu, Chengzhou
Abstract : Ternary PtRuCu aerogels were facilely synthesized by one-step in situ reduction, which exhibited good electrochemical performance for methanol oxidation. Abstract : Ternary PtRuCu aerogels are facilely synthesized by one-step in situ reduction. The formation of ternary PtRuCu aerogels can be completed within 2 hours owing to the accelerated gelation kinetics. Because of the unique porous architectures and synergistic effect, the optimized Pt4 Ru1 Cu5 aerogels exhibited good electrochemical performance for methanol oxidation reaction.